Pelaksanaan Kurikulum Dipelajari oleh Pelajar Pendidikan Islam di Kolej Pengajian Islam Selatan Thailand - Binhassan, Abdulrasyid; Salae, Mahsdi; Syarif Hayisama-ae, Muhammad; Chapakia, Fathiyah (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2023)
This study aims to examine how the implementation of curriculum in Islamic studies colleges, public universities in the South of Thailand. A curriculum audit was adapted to explain the curriculum studied. The design of this study uses a qualitative case study method involving as many as nine students from an Islamic studies college in the south of Thailand selected as study participants. The main criterion for the selection of the study participants was that the students were following the subject of Islamic education based on the informants' information. The method of data retrieval is made by interview, observation and document analysis, the data which is